A prospective study evaluating the impact of implementing the ERAS protocol on patients undergoing surgery for advanced ovarian cancer. Issue 3 (4th January 2019) - Agarwal, Reshu; Rajanbabu, Anupama; P V, Nitu; Goel, Gaurav; Madhusudanan, Lipi; U G, Unnikrishnan
Abstract : Objective: Information on the benefits of enhanced recovery after surgery (ERAS) when applied to advanced ovarian cancer() is minimal. The study objectives were to prospectively evaluate whether the implementation of ERAS in AOC patients improves post-operative recovery, and reduces the length of hospital stay (LOHS), without increasing the readmission rate or surgery-related complications; and to investigate ERAS protocol compliance. Methods: This was a prospective interventional study carried out at a single university teaching hospital. Patients undergoing laparotomy for advanced ovarian cancer (stages IIb–IV) from March 2017 to February 2018 were managed using an ERAS protocol. The conventional management (CM) period extended from January 2016 to December 2016. The primary outcome was reduction in LOHS. Secondary outcomes were ERAS protocol compliance, incidence of post-operative complications, and readmission rate. Results: The CM and ERAS groups each comprised 45 patients. Both the groups were comparable in terms of clinicopathological and operative characteristic. Median LOHS of the full cohort, primary debulking cohort, interval debulking cohort, staging surgery cohort (all 6 vs 4 days; p<0.001), and complex cytoreductive surgery cohort (5 vs 4 days; p=0.019) were significantly reduced in the ERAS group. The overall compliance for the ERAS protocol was 90.6%. Occurrence of moderate or severe (17.8% vs 0%; p=0.003) and ≥grade 2 extended Clavein-Dindo complications (22.2% vs 0%; p=0.001); and hospital stay due to occurrence of complications (31.1% vs 2.2%; p<0.001) were also significantly reduced in the ERAS group. There was no difference in the 30-day readmission rates. Conclusion: The results from our investigation suggest that the ERAS program can be successfully implemented in advanced ovarian cancer patients even in low-resource settings provided the program is modified to meet local needs so as not to increase healthcare costs.